PENGARUH LIKUIDITAS, OPINI TAHUN SEBELUMNYA DAN UKURAN PERUSAHAAN TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN TRANSPORTASI DAN LOGISTIK INDONESIA - Saputra, Jodi; Hasanah, Ade Nahdiatul (SUBSTANSI, 2024)
This study aims to examine the effect of liquidity, previous audit opinion and size company to the audit opinion going concern of Indonesian transportation and logistics company listing on the Indonesian stock exchanges (IDX).  All populations has through by purposive sampling data, we get 12 companies was obtained in 3 years of observation (2019-2021). The study focused on quantitative methods through associative descriptive approach obtained 3 hypothesis, where H1 is liquidity through proxy current ratios (CR) declared no effect on the audit opinion going concern, H2 the results of the previous year's audit opinion expressed effect on the audit opinion going concern and H3 the size of the company through the ratio of total assets declared no effect on the audit opinion going concern.